2015
DOI: 10.1002/2015tc003973
|View full text |Cite
|
Sign up to set email alerts
|

A crustal‐scale view at rift localization along the fossil Adriatic margin of the Alpine Tethys preserved in NW Italy

Abstract: Fossil rifted margins, whereby originally extended continental crust is subsequently stacked in orogenic belts, provide the opportunity to track rift-related tectonics across different crustal levels. In this study, the tectonothermal evolution of the fossil Adriatic continental margin, sampled in the Italian Southern Alps, is investigated combining new (U-Th)/He zircon (ZHe) thermochronology from upper crustal rocks with existing data from the originally underlying lower crust, to shed light on the processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 82 publications
(170 reference statements)
5
85
0
Order By: Relevance
“…The Mesozoic sedimentary record of the western Southalpine is extremely lacunous if compared to the successions of the Lombardian basin. This marked difference has been described in the literature (Beltrando, Stockli, et al, ; Berra et al, ; Fantoni et al, ). The syn‐rift sequence is visible only at selected locations.…”
Section: Southern Adriatic Marginmentioning
confidence: 62%
See 2 more Smart Citations
“…The Mesozoic sedimentary record of the western Southalpine is extremely lacunous if compared to the successions of the Lombardian basin. This marked difference has been described in the literature (Beltrando, Stockli, et al, ; Berra et al, ; Fantoni et al, ). The syn‐rift sequence is visible only at selected locations.…”
Section: Southern Adriatic Marginmentioning
confidence: 62%
“…The depositional age for these sandstones has been determined by palinomorphs as Pliensbachian‐Toarcian (Berra et al, ). Interestingly, (U‐Th)/He analysis on zircons in volcanic grains of the sandstone gave comparable absolute cooling ages (171 ± 14 Ma and 177 ± 14 Ma, respectively, for Fenera and Sostegno; Beltrando, Stockli, et al, ). These data demonstrate that the process of exhumation, cooling, erosion, and sedimentation was very rapid.…”
Section: Southern Adriatic Marginmentioning
confidence: 87%
See 1 more Smart Citation
“…Geologically, the Monte Fenera succession lies almost horizontally over the metamorphic basement (the “Serie dei Laghi”). From bottom to top, the following main geological formations are identified (Beltrando, Stockli, Decarlis, & Manatschal, ; Berra, Galli, Reghellin, Torricelli, & Fantoni, ; Fantoni & Fantoni, ): Permian Volcanic Complex (lava, tufa and other volcanic or pyroclastic rocks, 100–200‐m‐thick); Triassic gray/green sandstone (mostly quartzarenite), with intercalations of pelite and doloarenite (“Fenera Annunziata Sandstone” formation, few meters thick); about 300‐m‐thick succession mostly consisting of dolostone, with thin intercalations of clay, dolorudite and thin volcanoclastic horizons, dating from the Middle Triassic (“San Salvatore Dolomite” formation). A stratigraphic hiatus marks the Upper Triassic, while the Jurassic is represented by a thin basal unit of limestone/dolomite breccia (“Brecce del Monte Fenera”), covered by a Sinemurian formation of sandstone and microconglomerate (“San Quirico Sandstone,” 25–60‐m‐thick) and by the thick (about 250 m) Pliensbachian layers of the “Calcari spongolitici” formation, which consist of limestone with chert nodules and lenses (mostly spongolite) and intercalations of sandstone.…”
Section: The Ciota Ciara Cave: Site Presentationmentioning
confidence: 99%
“…Understanding the factors controlling decoupling, coupling and hyperextension should provide critical information on the mechanics of lithospheric necking and breakup. This exercise is critical at a time when new thermochronological data of fossil magma‐poor margins in the Alps and the Pyrenees have shown that reheating of the crust and the sediments occurs during lithospheric necking (thinning; Smye & Stockli, ; Beltrando et al, ; Seymour et al, ; Hart et al, ; Smye et al, ). Some authors suggest that these thermal events can be explained by rapid, active mantle upwelling during necking (Smye et al, ) and suggest that structures coupling fault in the crust and mantle are linked to both hyperextension and an actively upwelling mantle that could increase heat flow at the base of the extending crust and mantle lithosphere (Chenin et al, ; Gallacher et al, ; Hart et al, ; Huismans & Beaumont, , ; Royden & Keen, ; Svartman Dias et al, , ).…”
Section: Introductionmentioning
confidence: 99%